Production and purification of an Endo–1,4-beta-Xylanase from Humicola grisea var. thermoidea by electroelution - Monti, Rubens [UNESP]; Cardello, Leonardo [UNESP]; Custódio, Marcos F. [UNESP]; Goulart, Antonio J. [UNESP]; Sayama, Adriana H. [UNESP]; Contiero, Jonas [UNESP] (Sociedade Brasileira de Microbiologia, 2003)
Humicola grisea var. thermoidea produz duas formas de xilanase extracelular. A componente forma 1 foi purificada usando o método de eletroeluição devido à baixa produção desta enzima extracelular. A aparente massa molar foi determinada 61,8 kDa por SDS-PAGE.

Humicola grisea var. thermoidea produces two forms of extracellular xylanase. The component form 1 was purified using the electroelution method, due to the very small production of this extracellular enzyme. The apparent molecular mass was 61.8 kDa by SDS-PAGE.
Produção e purificação de uma Endo–1,4-beta-Xylanase de Humicola grisea var. thermoidea por eletroeluição
Keywords: eletroeluição; Humicola grisea var. thermoidea; purificação de enzimas; xilanase extracelular; electroelution; enzyme purification; extracellular xylanase; Humicola grisea var. thermoidea